EVALUASI KEBIJAKAN AKSI KONVERGENSI PADA PERCEPATAN PENURUNAN STUNTING DI KOTA ADMINISTRASI JAKARTA BARAT - Agus Romadhon; Harits Hijrah Wicaksana (Universitas Jenderal Ahmad Yani, 2025)
Stunting is a long-term health problem that hinders children's growth and development and is a critical issue in human resource development in Indonesia. This study investigates the convergence action policy to examine how stunting reduction has improved in West Jakarta. A descriptive qualitative method was employed in this study, collecting data through interviews, observations, and documentation studies with relevant informants. The Bernard method was used for data analysis, which included data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the convergence action policy in West Jakarta has not been optimal due to sectoral egos among regional agencies, poor coordination, and uneven understanding of the policy in the field. Although nutrition interventions and cross-sectoral engagement have increased, the eight convergence actions have not been fully successful. This study demonstrates that the policy to accelerate stunting reduction relies heavily on inter-agency collaboration, improved human resource capacity, and an integrated data management system.